Catalytic degradation of high density polyethylene over microporous and mesoporous materials - Pierella, Liliana Beatriz (2005)
High-density polyethylene (HDPE) was converted to a mixed of lower and higher hydrocarbons over micro (ZSM-11 zeolite with MEL structure) and mesoporous (MCM-41) modified materials. The main liquid hydrocarbons (LHC) were: benzene, toluene, xylenes (BTX), using Zn-, Mo-, and H-containing MEL-zeolites as catalysts. The Zn-zeolite exhibited the highest levels of LHC (>57 wt%) with BTX selectivity of 47 wt%. H-zeolite gave a higher fraction of gaseous hydrocarbons (C1-C4) than Mo- and Zn-zeolites. Zn-MCM-41 produced mainly C5-C16 products. LPG (C3-C4) levels were interesting for all the samples. Thermo gravimetric analyses studies of mixtures catalyst/polymer, have been used to investigate the performance of different catalysts on degradation reactions of the polymer. The catalytic transformation of the polyolefin occurs at lower temperature with respect to thermodecomposition of the pure HDPE (500 °C). A one-pass reactor in the temperature range of 410-500 °C and atmospheric pressure was employed. We observed the complete conversion of HDPE, in the range of temperatures studied (410-500 °C). The synthesized and modified samples after cation incorporation were characterized by TG-DSC, XRD, TPD-FID, FTIR and surface area by BET, in order to verify and to confirm the crystallinity (for microporous materials) and regularity (for mesoporous materials) of the structures, stability and the type of active sites. The reactant was characterized by FTIR, XRD and TG-DSC. Reaction products were analyzed by gas chromatography. By means of development of a competitive catalytic system, we determine the feasibility of the process of degradation of HDPE remainders towards the synthesis of gaseous and liquid hydrocarbons. © 2005 Elsevier Inc. All rights reserved.